From memory impairment to two occluders in the heart – a multidisciplinary case report - Wiśniewski , A.; Filipska , K.; Ekkert , A. (Neurologijos seminarai, 2021)
Transient global amnesia (TGA) is a rare cause of a sudden onset of confusion and anterograde amnesia. It is considered of ischemic, epileptogenic, or venous origin. The etiology is uncertain, although hipertension, hiperlipidemia, and ischemic heart disease are considered as possible mechanisms. The impact of stress, migraine, physical effort is also highlighted. In contrast to ischemic stroke, atrial fibrillation (AF) and patent foramen ovale (PFO) are relatively rarely reported in the pathophysiology of acute memory impairment. In most cases, no visible lesion is detected on neuroimaging. This case report presents a 62-year-old woman with TGA symptoms who had an acute left temporal lobe ischemic lesion confirmed by diffusion-weighted imaging sequence of magnetic resonance imaging. Extensive workup revealed coexistence of AF and PFO. Due to intolerance to oral anticoagulants, percutaneous closure of left atrial appendage and PFO was performed within two months. Combined heart interventions have proven to be a safe and efficient therapeutic option for secondary stroke prevention in this patient. This case illustrates that patients with sudden memory impairment require careful observation and extensive workup, as well as a multidisciplinary approach and treatment.